INVESTIGATING VARIABLE RBE IN A 12C MINIBEAM FIELD WITH MICRODOSIMETRY AND GEANT4. Issue 1 (21st January 2019) - Debrot, Emily; Bolst, David; James, Benjamin; Tran, Linh; Guatelli, Susanna; Petasecca, Marco; Prokopovich, Dale A; Reinhard, Mark; Matsufuji, Naruhiro; Jackson, Michael; Lerch, Michael; Rosenfeld, Anatoly B
Abstract: An experimental and simulation-based study was performed on a 12 C ion minibeam radiation therapy (MBRT) field produced with a clinical broad beam and a brass multi-slit collimator (MSC). Silicon-on-insulator (SOI) microdosimeters developed at the Centre for Medical Radiation Physics (CMRP) with micron sized sensitive volumes were used to measure the microdosimetric spectra at varying positions throughout the MBRT field and the corresponding dose-mean lineal energies and RBE for 10% cell survival (RBE10 ) were calculated using the modified Microdosimetric Kinetic Model (MKM). An increase in the average RBE10 of ∼30% and 10% was observed in the plateau region compared to broad beam for experimental and simulation values, respectively. The experimental collimator misalignment was determined to be 0.7° by comparison between measured and simulated microdosimetric spectra at varying collimator angles. The simulated dose-mean lineal energies in the valley region between minibeams were found to be higher on average than in the minibeams due to higher LET particles being produced in these regions from the MSC. This work presents the first experimental microdosimetry measurements and characterisation of the local biological effectiveness in a MBRT field.